Programmable Reflection–Transmission Shared‐Aperture Metasurface for Real‐Time Control of Electromagnetic Waves in Full Space - Bao, Lei; Ma, Qian; Wu, Rui Yuan; Fu, Xiaojian; Wu, Junwei; Cui, Tie Jun (Advanced science, 2021)
Recently, programmable metamaterials or metasurfaces have been developed to dynamically edit electromagnetic waves for realizing different functions in the same platform. However, the proposed programmable metasurfaces can only control reflected or transmitted wavefronts in half‐space. Here, a “Janus” digital coding metasurface with the capabilities to program various electromagnetic functions in the reflected (with R‐codes) and transmitted (with T‐codes) waves simultaneously is presented. Three PIN diodes are employed to design the metaparticle, and the state of the PIN diodes can be switched to change the reflected and transmitted phases independently. Three schemes achieved by the proposed programmable metasurface are provided as illustrative examples, including anomalous deflections, beam focusing, and scattering reduction in the full space. As a proof‐of‐concept, a prototype composed of 10 × 20 metaparticles is fabricated and the measured results are in good agreement with the designs and numerical results, validating the full‐space modulations enabled by the programmable metasurface. It is expected that the new programmable metasurface can broaden the applications in stealth technologies, imaging systems, and the next generation of wireless communications. A “Janus” coding programmable metasurface is proposed to edit the reflected and transmitted waves simultaneously in real‐time. Benefiting from the design of the separated current paths of diodes, the reflected and transmitted phases can be controlled independently in different polarizations. The proposed metasurface can implement various electromagnetic functions in the reflected (with R‐codes) and transmitted (with T‐codes) regions simultaneously.